Determining the peak spatial-average specific absorption rate (SAR) in the human body from wireless communications devices, 30 MHz to 6 GHz. General requirements for using the finite-difference time-domain (FDTD) method for SAR calculations Part 1, (16th January 2020) - British Standards Institution,
No abstract available